2020
DOI: 10.3390/microorganisms8030403
|View full text |Cite
|
Sign up to set email alerts
|

Differential Analysis of Proteins Involved in Ester Metabolism in two Saccharomyces cerevisiae Strains during the Second Fermentation in Sparkling Wine Elaboration

Abstract: The aromatic metabolites derived from yeast metabolism determine the characteristics of aroma and taste in wines, so they are considered of great industrial interest. Volatile esters represent the most important group and therefore, their presence is extremely important for the flavor profile of the wine. In this work, we use and compare two Saccharomyces cerevisiae yeast strains: P29, typical of sparkling wines resulting of second fermentation in a closed bottle; G1, a flor yeast responsible for the biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…The rest of the specific biological processes identified under MFP (−) presented a protein frequency between 2 and 0.1% ( Figure 2 ). These results were in contrast with the cell viability analysis: under without overpressure 5.53 × 10 6 (±2.1 × 10 6 ) CFU/mL, (10.64 ± 0.02% v / v ethanol) and under CO 2 overpressure 8.02 × 10 6 (±1.4 × 10 6 ) CFU/mL (3 bar, semi-sparkling wine, 10.85 ± 0.04% v / v ethanol), no significant differences were observed [ 31 ]. This suggests that the fundamental processes of cell growth and those related to the central metabolism of yeast would be taking place under both conditions, and in this case, the CO 2 overpressure would not affect cell viability, despite being subjected to stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the specific biological processes identified under MFP (−) presented a protein frequency between 2 and 0.1% ( Figure 2 ). These results were in contrast with the cell viability analysis: under without overpressure 5.53 × 10 6 (±2.1 × 10 6 ) CFU/mL, (10.64 ± 0.02% v / v ethanol) and under CO 2 overpressure 8.02 × 10 6 (±1.4 × 10 6 ) CFU/mL (3 bar, semi-sparkling wine, 10.85 ± 0.04% v / v ethanol), no significant differences were observed [ 31 ]. This suggests that the fundamental processes of cell growth and those related to the central metabolism of yeast would be taking place under both conditions, and in this case, the CO 2 overpressure would not affect cell viability, despite being subjected to stress.…”
Section: Resultsmentioning
confidence: 99%
“…These GO Terms could be involved with the maintenance of the redox balance between NAD + and NADH in aerobic conditions by S. cerevisiae . Yeasts need to recycle NAD + and oxidize NADH for the continuation of glycolysis; otherwise, the glycolytic flow would decrease, which could lead to a depletion of the ATP energy charge, becoming lethal for yeast [ 31 , 32 ]. According to Kutyna et al [ 33 ], most of the NADH produced during glycolysis is subsequently oxidized during the formation of ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme is excreted into the periplasmic space, where the hydrolysis occurs, and letting the monosaccharide products of the reaction, glucose and fructose, be transported into the cell. Higher Suc2p contents at EF in the flor yeast may be associated to a higher cell wall degradation that correlates with higher autolysis proteins compared to the conventional strain [18,23].…”
Section: Glycolysis/gluconeogenesis Proteomementioning
confidence: 99%
“…These cell adhesive properties allow the winemakers to easily remove yeasts and sediment in the "degüelle" phase during the production of cava by the traditional method. Moreover, previous studies have demonstrated that flor yeast is a good candidate for sparkling wine elaboration because they produce volatile compounds, such as higher alcohols, aldehydes, esters and ketones, and its influence on the wine final aroma [17,18]. The use of flor yeast could reduce production cost and time, marking a significant step forward in the sparkling wine industry.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the same authors proposed that the use of flor yeast in sparkling wine production would be interesting considering its fast cell death during the process [ 4 ]. Moreover, Gonzalez-Jimenez [ 5 ] reports that flor yeast may be proposed for sparkling wine production to enhance the diversity and typicity of sparkling wine yeasts. Wine quality needs to be controlled by preventing the development of spoilage microorganisms.…”
mentioning
confidence: 99%